Effect of froth rheology on froth and flotation performance. (January 2018) - Li, Chao; Runge, Kym; Shi, Fengnian; Farrokhpay, Saeed
Highlights: Froth viscosity was positively correlated to froth height above the lip. Air recovery was significantly affected by froth viscosity. Silica recovery was correlated to froth viscosity. Abstract: It has been suspected for some time that froth rheology has an impact on froth and flotation performance but little experimental work has been performed to investigate these effects. In this paper, the effect of froth rheology on froth and flotation performance was investigated by performing flotation tests in a 20 L continuous flotation cell using a synthetic ore which was a mixture of pure chalcopyrite and silica. Froth rheology was measured during these tests along with key flotation performance indicators: froth height above the lip, air recovery and silica recovery. It was found that froth rheology was positively correlated to froth height above the lip. Air recovery was also correlated to froth rheology; at low froth viscosity, air recovery increased upon increasing consistency index (a measure of the viscosity of a fluid) while the opposite was found at high froth viscosity. A similar correlation between froth viscosity and silica recovery was also observed. Measurements of froth rheology were also performed in industrial scale flotation cells processing a platinum ore. The investigated industrial scale froth exhibited similar rheological characteristics to that observed in the laboratory work. Both of the froths have a shear-thinning nature with minor yield stress. Froth height above the lip was also found to be positively correlated with froth viscosity, which supports the conclusions drawn from the laboratory work.